The impact of social media marketing activities on customer purchase intention: a study of the property industry in Malaysia - Ho, Li Shee; Zakaria, Nadisah; Foo, Siong Min (Emerald, 2024)
Purpose This study investigates the impact of social media marketing activities on customer purchase intention in the Malaysian property market.